Har Paulus Helie forfattet et skrift imod de københavnske teologer i 1544? - Jørgensen, Kaare Rübner (Kirkehistoriske Samlinger, 2016)
I 1543 blev kannikerne i Lund indkaldt til en samtale af professorerne i København. Da hensigten med denne var at få dem til at underkaste sig den lutherske kristendomsopfattelse, afviste de i en skrivelse året efter at møde op. Ifølge Erik Sjøberg skulle denne skrivelse være forfattet af den kendte katolske teolog Paulus Helie (Poul Helgesen). I det følgende undersøges samdsynligheden af denne tese. English Summary In 1543 the cannons of Lund Cathedral were invited to a talk by the Lutheran professors of Copenhagen. However, in a letter, issued the following year, the cannons refused to follow the invitation as the purpose of the talk was to achieve their acceptance of the Lutheran religion. On the basis of an analysis of the letter’s content and language historian Erik Sjøberg has argued that it might have been written in the name of the cannons by the famous Catholic reformer, the Carmelite friar Paulus Helie. In this paper I take his views and arguments up to revaluation.